2012
DOI: 10.1016/j.jhep.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sorafenib in patients with advanced hepatocellular carcinoma: Subanalyses of a phase III trial

Abstract: These exploratory subgroup analyses showed that sorafenib consistently improved median OS and DCR compared with placebo in patients with advanced HCC, irrespective of disease etiology, baseline tumor burden, performance status, tumor stage, and prior therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
570
3
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 742 publications
(616 citation statements)
references
References 40 publications
(50 reference statements)
21
570
3
11
Order By: Relevance
“…However, this statement requires strong qualification in light of the clinical evidence. In the SHARP trial, 11 sorafenib was associated with a median overall survival of 14.5 months among 54 patients with intermediate-stage HCC-only 3.1 months longer than the median survival of 11.4 months reported for the 51 patients in the placebo group. In addition, the GIDEON study 12 observed that sorafenib therapy was associated with adverse events in 69% and 66% of patients with intermediate-stage and advanced-stage disease, respectively; the correspond ing rates of serious adverse events were 32% and 38%.…”
Section: Correspondencementioning
confidence: 76%
“…However, this statement requires strong qualification in light of the clinical evidence. In the SHARP trial, 11 sorafenib was associated with a median overall survival of 14.5 months among 54 patients with intermediate-stage HCC-only 3.1 months longer than the median survival of 11.4 months reported for the 51 patients in the placebo group. In addition, the GIDEON study 12 observed that sorafenib therapy was associated with adverse events in 69% and 66% of patients with intermediate-stage and advanced-stage disease, respectively; the correspond ing rates of serious adverse events were 32% and 38%.…”
Section: Correspondencementioning
confidence: 76%
“…Sorafenib got approval for advanced HCC based on pivotal randomized phase III trials, however the majority of the patients in these trials were in good ECOG PS and most had Child Pugh A status, which is not the case in routine general practice. 21,22 Kostner et al in their retrospective study of sorafenib in HCC, noted median OS of only 1.8 months of patients in PS 2-3. 23 In our study, 66% of our patients had PS≥2.…”
Section: Tumor Characteristicsmentioning
confidence: 99%
“…Those results have been prospectively confirmed in different clinical trials in which sorafenib was the control arm (93)(94)(95)(96)(97) as well as in multiple prospective studies in real life clinical practice (98-100). Furthermore, sorafenib is able to maintain its efficacy despite the etiology of liver disease, the baseline status of neoplasm, the presence or absence of cancer related symptoms or previous therapies (101). Despite the success of sorafenib at advanced stage, there are still many aspects to be clarified.…”
Section: Improvements In the Treatment Of Intermediate-advanced Hccmentioning
confidence: 99%